The Power of Expectations in School Management: Pygmalion Effect - Gunduzalp, Seda; Ozan, Mukadder Boydak (Nesibe Aydin Education Inst, 2019)
This study aims to discover the pygmalion effect, which suggests to affect a person's expectations from other people on the actions of those people, by taking the opinions of primary school teachers. In order for the study to reach its goal, triangulation technique, which is a mixed method design, has been used. A likert-type five-point scale made up of 18 items and a semi-structured interview form comprising two open-ended questions have been used to acquire data. The scale has applied to take the opinions of teachers working at the schools administered by 25 managers mastering in a postgraduate program without thesis at the Education Management Inspection Planning and Economy Department of Firat University Institute of Education Sciences. The quantitative and qualitative data acquired have been analyzed by means of statistical softwares. It has been concluded from the findings acquired from teachers' views reveal the reality and accuracy of pygmalion effect in the field of education, and show that high expectations pave the way for teachers' motivation, effort, active working, commitment as well as the growth of their enthusiasm. It is seen that high expectations will generally reveal high performance, while low expectations, due to their negative effects on employees, will cause decrease in motivation as well as unwillingness towards the job being done and therefore, a decline or stability in performance.
Keywords: Pygmalion effect; expectation; school; management; triangulation